Digital Legitimacy: A Narrative Analysis of the Utilization of Management Information Systems for CSR Program Transparency in Public Companies - Tjiwidjaja, Halim (Jurnal Ar Ro'is Mandalika (Armada), 2025)
The increasing demands for transparency and social accountability in the digital era have encouraged public companies to utilize Management Information Systems (MIS) in managing their Corporate Social Responsibility (CSR) programs. This study aims to explore how MIS is used not only as an operational tool but also as a strategic means to build digital legitimacy in the eyes of stakeholders. This study uses a qualitative approach with a systematic literature review to analyze (1) the legitimacy narrative built by management through MIS, (2) the challenges of CSR data integration, and (3) the changing dynamics of communication between companies and stakeholders. The data used are sourced from content analysis of public secondary data from two public companies in the mining sector, PT. Tambang Emas Nusantara and banking, PT. Bank Mandiri. The findings of this study indicate that the companies build narratives of "Technocratic Accuracy" and "Total Transparency" through the use of online sustainability dashboards and reports. However, the main challenge faced is the standardization of qualitative data in CSR reports. In addition, the use of MIS has also transformed corporate communication into a more dialogic one, especially through social media, although this creates an expectation of instant responses from the company. The conclusion of this study indicates that digital legitimacy is formed through transparency narratives curated and disseminated by information systems. This research highlights the importance of a more organic integration between CSR strategies, communications, and information technology to build authentic and credible legitimacy in the eyes of stakeholders.